Morfo-funktsional'nye osobennosti zhenshchin-sportsmenok v aspekte polovogo dimorfizma - Socha, T. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The aim of the study was to reveal the peculiarities of women' morpho-functional systems displaying in sports occupations. The research was carried out during 1991-2001. The morphological features of the women athletes were investigated. The material for the study had served the data of the monitoring of the somatometric parameters of men and women participating in the Athletic Championships of Poland and divided in three age categories: 16-17 years, 18-19 years and higher 19 years. The carried out researches have allowed to estimate the age distinctions of the structure of a body of women engaged in various kinds of athletics. The structure of a body was estimated in view of 23 somatometric parameters. Total researched 556, including 218 women. The analysis of the results of the carried out research allows to conclude: 1. The dimorphic features of a structure and functions of a female organism renders the versatile influence on sports engineering, tactics and productivity, that causes the necessity of permanent specification of the contents of training influences at organization of their special physical, technical and tactical preparation. 2. The exact knowledge of qualitative and quantitative parameters of distinctions in the females and males allows to use results of the newest scientific - theoretical development both technological achievement of the theory and technique of sports preparation more effectively, bringing in the appropriate corrections in the processes of their development and realizations at organization of sports training of the women.